The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4238/2015.november.13.16
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of native and invasive Plagioscion squamosissimus (Perciformes, Sciaenidae) populations in Brazilian hydrographic basins

Abstract: ABSTRACT. The genetic diversity of invasive and native populations of Plagioscion squamosissimus (Heckel, 1840) from the Paraná, Parnaiba and Araguaia-Tocantins river basins was assessed by using Random Amplified Polymorphic DNA (RAPD) markers. Genetic data confirmed the hypothesis of low genetic variability within and among P. squamosissimus populations introduced in the upper Paraná River basin, and indicated that they likely originated from a common ancestor. Moreover, the data demonstrated that, in agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(36 reference statements)
1
2
1
Order By: Relevance
“…P. squamosissimus successfully colonised all the habitats of the Paraná River basin (Agostinho et al, ), despite the low genetic diversity rates observed in the current analyses and by Panarari‐Antunes et al . (, ).…”
Section: Collection Sites and Number Of Specimens Plagioscion Squamossupporting
confidence: 68%
See 2 more Smart Citations
“…P. squamosissimus successfully colonised all the habitats of the Paraná River basin (Agostinho et al, ), despite the low genetic diversity rates observed in the current analyses and by Panarari‐Antunes et al . (, ).…”
Section: Collection Sites and Number Of Specimens Plagioscion Squamossupporting
confidence: 68%
“…In the case of introduced P. squamosissimus populations, others factors may also be related to its successful invasion. P. squamosissimus successfully colonised all the habitats of the Paraná River basin (Agostinho et al, 2008), despite the low genetic diversity rates observed in the current analyses and by Panarari-Antunes et al (2012, 2015.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Plagioscion squamosissimus from the Upper Paraná River Basin shares a single haplotype with populations from the Parnaíba River, revealing that P. squamosissimus offspring from the Parnaíba River Basin occur only in the Paraná River Basin and have low kinship with the populations of the Amazon River Basin (Panarari-Antunes et al 2012). According to Panarari-Antunes et al (2012, 2015 and Diamante et al (2017), the non-native populations of P. squamosissimus from the Upper Paraná River Basin and the native population of the Parnaíba River, have low polymorphism and high genetic similarity. These populations of P. squamosissimus, however, differ genetically from the Araguaia-Tocantins native population, which is the most basal and polymorphic population.…”
Section: Studiesmentioning
confidence: 99%